Costs of Growing Coffee (Coffea Arábiga L.) Production, Profits and Unit Cost in the Municipality of Amatepec, State of México. 2023 - Hernández, José Luis Morales; Reyes, Claudia Janeth Gómez; Razo, Felipe de Jesús González; Ramírez, Ma del Carmen Domínguez (Archives of Business Research, 2023)
The vast majority of coffee producers in the different states of the Mexican Republic, when asked how much it costs to produce cherry, parchment or roasted coffee per unit area, do not know and do not keep records of their costs. This leaves them unable to budget effectively and allocate resources during the year, putting them in a vulnerable situation in the face of changing markets and the supply and demand of national and international coffee. With the objective of presenting an overview of coffee costs, profit and unit costs, in the Municipality of Amatepec, a comparative field study was carried out with the producing states of Veracruz, Puebla, and Chiapas, during 2023. To obtain the costs A survey was applied to representative producers of the region chosen in a completely random sampling, then the FIRA methodology was used to determine total production costs in coffee cultivation. The results indicate that for the production season the activity of cultural work 25%, harvest with 24%, then fertilization with 21% and pest control contributes with 14%. As a result of prices and costs, the profits obtained in coffee cultivation are safer in parchment and roasting both for the Municipality of Amatepec, and in the states of Veracruz, Puebla and Chiapas with which the comparisons were made.